Evaluation of the Qawaid Fiqhiyyah Principle in Sharia Economic Development in Indonesia: Challenges and Opportunities - Heni Handriani; Muthoifin (Walidem Institute and Publishing (WIP), 2024)
This study aims to analyze the principles of Qawaid Fiqih applied in the implementation of sharia economics in Indonesia. Qawaid Fiqih is the basic rules in Islamic law that function as a normative foundation in various sharia economic activities. This study uses a qualitative approach with literature study methods and in-depth interviews to collect data from various sources, including government regulations, policies of Islamic financial institutions, and the views of Islamic economists. The results of the study show that the principles of Qawaid Fiqih, such as al-Dharar yuzal (danger must be eliminated), al-Masyaqqah tajlibu al-taysir (difficulty brings convenience), and al-Ghunm bil-ghurm (benefits are proportional to risks), play an important role in ensuring that sharia economic practices in Indonesia run following sharia principles. These principles are applied in various sectors, such as Islamic banking, Islamic insurance, and Islamic capital markets, and help overcome the regulatory and operational challenges faced by Islamic financial institutions. The study also identifies several challenges in the implementation of Qawaid Fiqih in Indonesia, including a lack of a deep understanding of these principles among Sharia economic practitioners and regulations that still need to be refined to support more effective implementation. These findings are expected to contribute to the development of more comprehensive and sustainable policies in supporting the growth of the Sharia economy in Indonesia. Overall, this study confirms that the proper implementation of Qawaid Fiqih can improve the efficiency and integrity of the sharia economic system in Indonesia. It is hoped that the results of this study can guide policymakers and practitioners in developing a better sharia economic system following Islamic values.